2015
DOI: 10.1039/c5tx00222b
|View full text |Cite
|
Sign up to set email alerts
|

Key mechanisms involved in ionizing radiation-induced systemic effects. A current review

Abstract: Organisms respond to exogenous threats and insults by a potent inflammatory and immune response, aimed at preserving tissue integrity and restoring tissue homeostasis and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 250 publications
(220 reference statements)
0
64
0
Order By: Relevance
“…Radiotherapy is genotoxic for tumour cells, but affects non‐targeted and non‐irradiated cells through changes in inflammatory and immune reactivity, as well as genomic instability. Gap junction proteins are disrupted and mediators such as reactive oxygen species, nitric oxide, cytokines and exosomes are released.…”
Section: Impact Of Neoadjuvant Therapymentioning
confidence: 99%
“…Radiotherapy is genotoxic for tumour cells, but affects non‐targeted and non‐irradiated cells through changes in inflammatory and immune reactivity, as well as genomic instability. Gap junction proteins are disrupted and mediators such as reactive oxygen species, nitric oxide, cytokines and exosomes are released.…”
Section: Impact Of Neoadjuvant Therapymentioning
confidence: 99%
“…At present, the paradigm is currently being questioned according to which the basic, biologically important effect of exposure to IR is DNA damage. It has been observed that radiation-induced biological effects cannot be explained exclusively by the exposure of cells or DNA to IR, but also concerns the cells which have not been directly exposed to IR (NTE) [39]. At present, it is considered that IR induces a complex systemic cellular response, including the following types of NTE: radiation-induced bystander effect (RIBE), radioadaptive response, and radiation-induced genomic instability (RIGI) [39].…”
Section: Specificity Of Female Gametogenesis and Studies Of Radiosensmentioning
confidence: 99%
“…It has been observed that radiation-induced biological effects cannot be explained exclusively by the exposure of cells or DNA to IR, but also concerns the cells which have not been directly exposed to IR (NTE) [39]. At present, it is considered that IR induces a complex systemic cellular response, including the following types of NTE: radiation-induced bystander effect (RIBE), radioadaptive response, and radiation-induced genomic instability (RIGI) [39]. The common feature of NTE is that direct nuclear exposure is not required for its occurrence, and it occurs within the range of low doses (below 1 Gy) [39]; thus, such doses which are equivalent to the environmental, chronic human exposure to IR.…”
Section: Specificity Of Female Gametogenesis and Studies Of Radiosensmentioning
confidence: 99%
“…For example, after exposure of cells to a genuine damaging agent like ionizing radiation even cells (bystander) that were not exposed directly to radiation may endure a significant level of damage with inflammation or the immune system to hold the orchestrating roles [2]. The resulting DNA, protein or lipid membrane damage can evoke the release of various 'danger signals' which can be of various nature and they are often called DAMPs (Damage Associated Molecular Patterns).…”
mentioning
confidence: 99%